2018
DOI: 10.4037/ajcc2018252
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Among Palliative Care, Ethical Climate, Empowerment, and Moral Distress in Intensive Care Unit Nurses

Abstract: Poor ethical climate, unintegrated palliative care teams, and nurse empowerment are associated with increased moral distress. The findings highlight the need to promote palliative care education and palliative care teams that are well integrated into intensive care units.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
115
2
18

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(145 citation statements)
references
References 25 publications
10
115
2
18
Order By: Relevance
“…One might hope interventional studies to empower nurses would decrease moral distress. Although this is a promising direction, a more recent study ( Altaker et al, 2018 ) suggested that nurses with lower perceived empowerment may feel less moral obligation, and therefore less moral distress. There remains a need for interventional studies exploring methods to ameliorate moral distress and enhance job satisfaction and healthy work environments for nurses.…”
Section: Phenomena Affecting Nurse Well-beingmentioning
confidence: 99%
“…One might hope interventional studies to empower nurses would decrease moral distress. Although this is a promising direction, a more recent study ( Altaker et al, 2018 ) suggested that nurses with lower perceived empowerment may feel less moral obligation, and therefore less moral distress. There remains a need for interventional studies exploring methods to ameliorate moral distress and enhance job satisfaction and healthy work environments for nurses.…”
Section: Phenomena Affecting Nurse Well-beingmentioning
confidence: 99%
“…High moral distress in nurses has been associated with burnout and higher turnover rates, as well as lower patient satisfaction with care (Rice, Rady, Hamrick, Verheijde, & Pendergast, 2008). Increased moral distress has also been correlated with a poorly rated ethical climate (Altaker, Howie-Esquivel, & Cataldo, 2018). Increased nurse involvement in communication and development of the plan of care with the patient, family, and health care team can improve the ethical climate and overall quality of care provided, as well as decrease moral distress (Altaker et al, 2018;Lasater et al, 2019).…”
Section: Improving End-of-life Care For Hospitalized Older Adultsmentioning
confidence: 99%
“…Increased moral distress has also been correlated with a poorly rated ethical climate (Altaker, Howie-Esquivel, & Cataldo, 2018). Increased nurse involvement in communication and development of the plan of care with the patient, family, and health care team can improve the ethical climate and overall quality of care provided, as well as decrease moral distress (Altaker et al, 2018;Lasater et al, 2019). Higher quality end-of-life care is also linked to better nurse practice environments, including factors such as nurse involvement in hospital aff airs, manager support, adequate staffi ng, and nurse-physician relationships (Lasater et al, 2019).…”
Section: Improving End-of-life Care For Hospitalized Older Adultsmentioning
confidence: 99%
“…Unresolved moral distress can lead to nurses' job dissatisfaction. 35 According to Ulrich, 36 in clinical situations, nurses who experience moral distress are more likely than others to deny responsibility for their actions and to blame nursing and hospital management for perceived problems in the work environment, so they will become increasingly dissatisfied with their work.…”
Section: Moral Distressmentioning
confidence: 99%
“…44 A unitbased approach offers a chance for multiple disciplines engaged in the care of a particular patient to access the consultation. 35 It is suggested that embedding a clinical ethicist in the interprofessional team can promote the dialog between medical professionals who must explore difficult choices. 45 Morally distressing situations almost always involve an interdisciplinary issue, such as a lack of effective communication between team members, or uncertainty about which medical service team is responsible.…”
Section: Moral Distressmentioning
confidence: 99%